2012
DOI: 10.1002/ccd.24505
|View full text |Cite
|
Sign up to set email alerts
|

First experience with andraStent XL implantation in children and adolescents with congenital heart diseases

Abstract: Our initial results show that AndraStents are implantable and efficacious in different vascular stenoses and present a valuable alternative to the available large stents. With the application of a modified front-loading technique, they can also be implanted in smaller children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…This series documents that this is a versatile stent family, which can be used for indications ranging from ductal stenting in a neonate to coarctation stenting in a teenager. The immediate results and complication rate are comparable with previous published series in the literature using different stent designs in patients with congenital heart disease .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This series documents that this is a versatile stent family, which can be used for indications ranging from ductal stenting in a neonate to coarctation stenting in a teenager. The immediate results and complication rate are comparable with previous published series in the literature using different stent designs in patients with congenital heart disease .…”
Section: Discussionsupporting
confidence: 83%
“…Thus, most pediatric cardiologists have looked at using stents initially designed for biliary or renal work. Such stents have nominal diameters of 5–10(12) mm and potentially can be dilated further . Ex vivo bench testing, in particular to look at shortening characteristics of these stents during over dilation has been pioneered by Ing and Stern .…”
Section: Introductionmentioning
confidence: 99%
“…Extremly tortous course of stenotic MAPCA could have been the reason for complete rupture of 1 stent in 6 months follow-up. Chest X-ray, CT-angiography and fl uorscopy could distinguish this complication (6). Successful implantation of 30XL Andrastent into fractured parts of previously implanted PG stent was performed consequently.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective multicentre trial involving 105 patients showed that the Cheatham Platinum stent is safe and effective [ 13 ]. Data on the safety and effectiveness of off-label stents are absent or limited to small retrospective studies [ 11 , 15 – 17 ]. The choice to implant a specific type of stent relies on clinical and anatomical characteristics of the patients such as age, diameter of the aorta and of the stricture, previous operations/interventions, site of the lesion and anatomy of adjacent aorta and aortic branches [ 18 ].…”
Section: Discussionmentioning
confidence: 99%